BALR-6 regulates cell growth and cell survival in B-lymphoblastic leukemia. Issue 1 (December 2015) - Rodríguez-Malavé, Norma; Fernando, Thilini; Patel, Parth; Contreras, Jorge; Palanichamy, Jayanth Kumar; Tran, Tiffany; Anguiano, Jaime; Davoren, Michael; Alberti, Michael; Pioli, Kimanh; Sandoval, Salemiz; Crooks, Gay; et al.
Abstract Background A new class of non-coding RNAs, known as long non-coding RNAs (lncRNAs), has been recently described. These lncRNAs are implicated to play pivotal roles in various molecular processes, including development and oncogenesis. Gene expression profiling of human B-ALL samples showed differential lncRNA expression in samples with particular cytogenetic abnormalities. One of the most promising lncRNAs identified, designated B-ALL associated long RNA-6 (BALR-6), had the highest expression in patient samples carrying the MLL rearrangement, and is the focus of this study. Results Here, we performed a series of experiments to define the function of BALR-6, including several novel splice forms that we identified. Functionally, siRNA-mediated knockdown of BALR-6 in human B-ALL cell lines caused reduced cell proliferation and increased cell death. Conversely, overexpression of BALR-6 isoforms in both human and mouse cell lines caused increased proliferation and decreased apoptosis. Overexpression of BALR-6 in murine bone marrow transplantation experiments caused a significant increase in early hematopoietic progenitor populations, suggesting that its dysregulation may cause developmental changes. Notably, the knockdown of BALR-6 resulted in global dysregulation of gene expression. The gene set was enriched for leukemia-associated genes, as well as for the transcriptome regulated by Specificity Protein 1 (SP1). We confirmed changes in the expression of SP1, as well as its known interactor and downstream target CREB1. Luciferase reporter assays demonstrated an enhancement of SP1-mediated transcription in the presence of BALR-6. These data provide a putative mechanism for regulation by BALR-6 in B-ALL. Conclusions Our findings support a role for the novel lncRNA BALR-6 in promoting cell survival in B-ALL. Furthermore, this lncRNA influences gene expression in B-ALL in a manner consistent with a function in transcriptional regulation. Specifically, our findings suggest that BALR-6 expression regulates the transcriptome downstream of SP1, and that this may underlie the function of BALR-6 in B-ALL.